2014
DOI: 10.3389/fmicb.2014.00556
|View full text |Cite
|
Sign up to set email alerts
|

Microbial succession and the functional potential during the fermentation of Chinese soy sauce brine

Abstract: The quality of traditional Chinese soy sauce is determined by microbial communities and their inter-related metabolic roles in the fermentation tank. In this study, traditional Chinese soy sauce brine samples were obtained periodically to monitor the transitions of the microbial population and functional properties during the 6 months of fermentation process. Whole genome shotgun method revealed that the fermentation brine was dominated by the bacterial genus Weissella and later dominated by the fungal genus C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
61
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 64 publications
3
61
0
3
Order By: Relevance
“…Microbial succession has been reported in different fermented foods, including idli (4,36,37). In idli batter, there was an initial growth of aerobic bacteria followed by microaerophilic LAB during succession (4).…”
Section: Discussionmentioning
confidence: 99%
“…Microbial succession has been reported in different fermented foods, including idli (4,36,37). In idli batter, there was an initial growth of aerobic bacteria followed by microaerophilic LAB during succession (4).…”
Section: Discussionmentioning
confidence: 99%
“…However, until date, no studies showing that microbes derived from doenjang‐meju are mainly responsible for ganjang fermentation have been conducted. Although there are a few reports that bacteria as well as archaea and fungi may be responsible for ganjang fermentation because traditional ganjang is prepared under high salt conditions and fungi are dominant microbes in doenjang‐meju fermentation (Kim and others 2013a,b; Jung and others ), most studies have suggested that bacteria contribute to a larger extent to the fermentation (Kim and others ; Wei and others 2013a,b; Sulaiman and others ). A preliminary study using qPCR and plate counting analysis showed that the abundance of archaea and fungi was indeed very low compared to that of bacteria in the ganjang samples during the entire fermentation period (data not shown), similar to reports on fermented fish products with a high salt concentration (Jung and others ; Lee and others 2014b).…”
Section: Discussionmentioning
confidence: 99%
“…Research on both the microbial communities and the associated metabolite production during ganjang fermentation is very important to gain a better understanding of the fermentation process and to prevent the production of undesirable metabolites. However, most previous studies were limited to a snapshot analysis of either the microbial communities or the metabolites of ganjang fermentation (Cho and Seo ; Tanaka and others ; Lee and others ; Wei and others 2013a,b; Sulaiman and others ). To date, no simultaneous studies on the microbial dynamics and metabolite changes during ganjang fermentation have been performed, although they would increase the understanding of the relationship between the microbial population and the metabolite production (Jeong and others ; Jung and others ; Lee and others 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…Sulaiman et al . () revealed the diversity of microorganism in different maturity of salami by HTS. Currently, Illumina MiSeq sequencing has achieved excellent results in the detection of microbial diversity in fermented food (Bokulich ).…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al (2014) discovered the gene sequence of extreme halophilic archaea isolated from pickled marine products by Illumina MiSeq. Sulaiman et al (2014) revealed the diversity of microorganism in different maturity of salami by HTS. Currently, Illumina MiSeq sequencing has achieved excellent results in the detection of microbial diversity in fermented food (Bokulich 2012).…”
Section: Introductionmentioning
confidence: 99%